Analysis of the autoimmune response to BP180 in Chinese stroke patients - Jing Wang; Hong Liu; Zhenzhen Wang; Qing Pan; Furen Zhang (Sociedade Brasileira de Dermatologia, 2023)
Abstract Background Significant association between bullous pemphigoid (BP) and stroke has been reported. This study aimed to evaluate the level of anti-BP180 antibody in stroke patients to explore the relationship between BP and stroke in their pathogenesis. Methods We collected serum samples from stroke patients and matched controls between February 2019 and June 2020. The anti-BP180 antibody levels were measured by enzyme-linked immunosorbent assay (ELISA). Results A total of 1183 stroke patients including 970 with cerebral infarction (CI), 192 with intracerebral hemorrhage (ICH), 21 with CI and ICH, and 855 controls were enrolled in this study. Anti-BP180 autoantibody values were significantly higher in stroke patients than in controls (p < 0.001). Anti-BP180 autoantibody-positive rates were 12.51% (148) in stroke patients and 4.68% (40) in controls (p < 0.001, OR = 2.65). In anti-BP180 autoantibody-positive subjects, the values were significantly higher in stroke patients than in controls (p < 0.001). However, only 10 (6.76%) stroke patients and 3 (7.5%) controls had high values (> 100 RU/mL) (p = 0.87). Stratified analysis showed that anti-BP180 antibody positive rates were independent of age, sex, and stroke subtypes in the stroke group. Positive rates in patients with both CI and ICH were nearly two times higher than those in patients with either CI or ICH alone (p = 0.11, OR = 1.94). Study limitations This study had a limited sample size and lacked quantitative criteria for stroke severity. Conclusions Anti-BP180 antibody values and positive rates were higher in stroke patients than in controls, suggesting that stroke patients may have higher of developing BP.